2020
DOI: 10.3389/fphys.2020.583862
|View full text |Cite
|
Sign up to set email alerts
|

A Scientific Rationale for Using Cystic Fibrosis Transmembrane Conductance Regulator Therapeutics in COVID-19 Patients

Abstract: Several pathological manifestations in coronavirus disease 2019 (COVID-19), including thick mucus, poor mucociliary clearance, and bronchial wall thickening, overlap with cystic fibrosis disease patterns and may be indicative of “acquired” cystic fibrosis transmembrane conductance regulator (CFTR) dysfunction. Indeed, tumor necrosis factor (TNF), a key cytokine driving COVID-19 pathogenesis, downregulates lung CFTR protein expression, providing a strong rationale that acquired CFTR dysfunction arises in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…These observations indicated that abnormal CFTR function might be a key factor predisposing to the development of severe pneumonia or recalcitrant airway microbial infections, and therefore, CFTR has been hypothesized as a therapeutic target of COVID-19. 13 Here, we stimulated the RECs with the SARS-CoV-2 structural proteins to investigate whether the CFTR-Cl − signaling pathway is implicated in exuberant airway inflammation caused by SARS-CoV-2 infection, and further elucidate the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…These observations indicated that abnormal CFTR function might be a key factor predisposing to the development of severe pneumonia or recalcitrant airway microbial infections, and therefore, CFTR has been hypothesized as a therapeutic target of COVID-19. 13 Here, we stimulated the RECs with the SARS-CoV-2 structural proteins to investigate whether the CFTR-Cl − signaling pathway is implicated in exuberant airway inflammation caused by SARS-CoV-2 infection, and further elucidate the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to our data that iOWH032 inhibits CFTR, another group reported this compound can paradoxically both inhibit and potentiate human CFTR heterologously expressed in Xenopus oocytes, depending on the concentration applied [ 33 ]. The basis for these activities and their relevance to in vivo effects is unclear, but these results suggest iOWH032 could have therapeutic benefit for other diseases, including cystic fibrosis [ 34 ], influenza [ 35 ], and COVID-19 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…[3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , ...…”
Section: Uncited Referencesunclassified
“…Thick mucus formation can become organized in the distal bronchioles and compromise local and then general ventilation characteristics, ultimately affecting gas-exchange at the alveoli apparatus. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]…”
Section: Guaifenesinmentioning
confidence: 99%